Nutripriming and mat thickness on tray nursery in rice - Ancy U A (Department of Agronomy, College of Horticulture, 2016)
Mechanized rice cultivation can play a vital role in transforming rice production of Kerala. In the context of labour shortage and growing commercialization of agriculture, mechanization is very important for ensuring timeliness and precision of operation. Mechanized transplanting is a key link to the entire mechanization of paddy cultivation. However, lack of standardization of tray nursery production technologies appears to be one of the major hurdles against the appropriate exploitation of transplanting machineries. Nutripriming is a novel seed invigoration technique which helps for early germination and quality seedling production. The present study entitled “Nutripriming and mat thickness on tray nursery in rice” was carried out during 2015-2016 at Agricultural Research Station, Mannuthy with the objectives of standardization of production technology of tray nursery in rice for mechanical transplanting and evaluation of efficiency of nursery technique under field condition. The study was conducted in three experiments using variety Jyothi. Experiment I was designed in factorial CRD with 18 treatment combinations, replicated thrice. Six media compositions viz. 40% rice husk charcoal (RHC) + 40 % Soil + 20 % vermicompost (VC), 60 %RHC+ 20 % Soil + 20 % coir pith compost (CPC), 60 % RHC+ 20 % CPC+ 20 % VC, 80 % RHC + 20 % CPC, 80 % RHC + 20 % VC, 80 % RHC + 20 % Soil and three levels of thickness viz. 10, 15 and 20 mm were studied in this experiment. The media composition 60 % RHC + 20 % Soil + 20 % CPC, 40 % RHC + 40 % Soil + 20 % VC and 80 % RHC + 20 % Soil with 10mm thickness of media were superior with regard to the biometric characters of seedlings and mat characteristics such as shearing strength and slippage. Cheap mat nursery was also produced by 60 % RHC+ 20 % Soil + 20 % CPC with10 mm thickness of media. The highest content of K was observed in seedlings produced with media of 40 % RHC + 40 % Soil + 20 % VC. Best performing three media viz. 40 % RHC + 40 % Soil + 20 % VC, 60 % RHC + 20 % Soil + 20 % CPC and 80 % RHC + 20 % Soil with 10mm thickness were selected from Experiment I and nutripriming treatments were imposed on these media in Experiment II. The experimental design was factorial CRD with three replications. Nutripriming treatments viz. priming with 0.1per cent urea, 0.01per cent borax, 0.05per cent ZnSO4, combinations of urea with borax and ZnSO4, combination of urea, borax and ZnSO4, 1per cent Pseudomonas fluorescens and 1per cent PGPR mix I were studied. All the three media performed similarly with respect to biometric characters at 15DAS. Media containing 60 % RHC + 20 % Soil + 20 % CPC produced seedlings with significantly higher content of N and K. Priming with urea and urea+ ZnSO4+ borax were superior with regard to biometric parameters and mat characteristics. Higher contents of K, S and Zn were observed in seedlings primed with urea + borax. However, seedlings produced by priming with urea + ZnSO4 + borax were superior with respect to Ca, Mg, Zn and B content. The cheaper nursery was produced by the combination of 60 % RHC + 20 % Soil + 20 % CPC media with urea priming. The best performing five treatment combinations viz. 80 % RHC + 20 % Soil + 0.1 % Urea, 80 % RHC + 20 % Soil + 0.01 % Borax , 40 % RHC + 40 % Soil + 20 % VC + 0.1 % Urea + 0.05 % ZnSO4 , 60 % RHC + 20 % Soil + 20 % CPC + 0.1 % Urea + 0.01 % Borax and 80 % RHC + 20 % Soil + 0.1 % Urea + 0.05 % ZnSO4 + 0.01% Borax from Experiment II were evaluated under field condition in Experiment III. The experimental design was RBD with four replications. All the treatment combinations performed similarly and were significantly superior to control with respect to growth and yield attributes. Grain and straw yields were also not influenced by any of the treatment combinations studied. The tray nursery produced with different combinations of media did not show any significant variation with respect to the performance of the transplanter. The treatment combinations 40 % RHC + 40 % Soil + 20 % VC with 0.1 % Urea + 0.05 % ZnSO4 and 60 % RHC + 20 % Soil + 20 % CPC with urea + borax recorded higher B: C ratio. From the detailed assessment of three experiments it was concluded that media containing 60 % RHC+ 20 % Soil + 20 % CPC with 10mm thickness and seeds primed with 0.1% Urea + 0.05 % ZnSO4 + 0.01 % Borax was effective for quality tray nursery production with respect to healthy seedlings, easiness in transport, performance of transplanter and cost of production.